Malignant syphilis in a patient with acquired human immunodeficiency virus (HIV) infection - Ana Sofia Pereira; Aluixa Lozada; Ana Filipe Monteiro (Sociedade Brasileira de Dermatologia, 2022)
Abstract Malignant syphilis is an uncommon variant of syphilis, most often (but not always) found in immunosuppressed individuals. This report describes the case of a 57-year-old man, infected with the acquired human immunodeficiency virus (HIV), with a generalized picture of erythematous-squamous papules that rapidly progressed to painful and ulcerated plaques and nodules, some covered with a black rupioid crust. The analytical study performed revealed positive VDRL (Venereal Disease Research Laboratory) and RPR (Rapid Plasma Reagin). The skin biopsy was nonspecific; however, the immunohistochemical analysis disclosed the presence of spirochetes. The patient was then treated with benzathine penicillin G 2.4 MU once a week IM for three weeks, with progressive resolution of the lesions. Considering its rarity, this atypical form of syphilis that needs to be known to better recognize its clinical presentation and provide more prompt treatment to patients.